Design rules, volume 2: how technology shapes organizations - Baldwin, Carliss Y. (Harvard Business School, 2019)
The purpose of this chapter is to use the theory of bottlenecks laid out in previous chapters to better understand the dynamics of an open standards-based platform. I describe how the Wintel platform evolved from 1990 through 2000 under joint sponsorship of Intel and Microsoft. I first describe a series of technical bottlenecks that arose in the early 1990s concerning the “bus architecture” of IBM-compatible PCs.Intel's management of buses demonstrates how, under conditions of distributed supermodular complementarity, a platform sponsor can reconfigure the modular structure of a technical system, property rights within the system, and its own zone of authority to increase system-wide throughput, while protecting its own strategic bottleneck from disintermediation.I go on to describe how Microsoft used platform envelopment to establish a second strategic bottleneck in productivity software and later to respond to the threat of disintermediation from platform-independent Internet browsers. I end the chapter by discussing the conditions under which shared platform sponsorship can be a long-term dynamic equilibrium
10.2139/ssrn.3482515
Keywords: Graue Literatur; open platforms; bottlenecks; Wintel platform; disintermediation; Hardware; Software; Business History; Computer Industry